Gestão de risco: a importância da resiliência em eventos indesejáveis - Lopes, Artur Cesar Sartori Lopes (2016)
Today, many tools with statistical data are used to evaluate dangers. On the other hand, people use the judgment to evaluate the risk, which is based on culture of risk. The perception of risk changes as the environment in which the person is immersed and differentiates between the cultures itself. The aim of this research is understand the role of the various actors involved in risk management and how resilience helps us with undesirable events. Eleven undesirable events were investigated with ten respondents, in six organizations, in order to identify and analyze how risk management, resilience and risk perception interact. The multifaceted analysis reinforced the importance of the resilient aspects for effective risk management. The possible participation of those people in the event, since the context of management, reinforced by shared control, identification of individual’s habilities, not prescribed, encouraging cooperation between those actors, effective communication and simplification of procedures are aspects integrators to risk management. For further research opportunities, reinforces the need to analyze aspects of organizational culture covering social sciences: anthropology, sociology, psychodynamics of work, ethics, sociology and country culture as a conscious agent and experiencer of reality.